AREA UNDER DISEASE PROGRESS CURVE AND INFLUENCE ABIOTIC FACTORS ON WILT OF POMEGRANATE - R. SOMU; R. K. MESTA; K. C. KIRAN KUMAR (The Bioscan, 2024)
Wilt of pomegranate caused by Ceratocystis fimbriatais the most destructive disease in pomegranate growing areas of the world. The field experiment was conducted in fixed plot to know the AUDPC,apparent rate of infection (r) and influence of weather factors on disease incidence. The per cent disease incidence was 10.00 in the month of October 2015 and it reached 82.50 at the end of September 2016. As the per cent disease increased the apparent rate of infection (r) value was also increased from 0.080 to 0.130. The area under disease progress curve reached 142.50 at the end of September 2016. The weather data collected during the experiment was subject to multiple regression and step wise multiple regression analysis.The data revealed that weather parameters influence R2 value of 44.00 per cent on per cent disease incidence. Step wise multiple regression analysis showed that among the weather parameters maximum variation was explained by rainfall (30.66 %).